ANALYSIS OF IMPLEMENTATION OF MALARIA CONTROL POLICY AT SIDODADI HEALTH CENTER ASAHAN DISTRICT - Syahruddin; Kasim, Felix; Saputri, Ika Nur (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Abstract Malaria is a serious and potentially fatal public health problem. Malaria elimination efforts are carried out in Indonesia to create a society that is free from malaria transmission in 2030. This study aims to analyze the implementation of malaria control policies at the Sidodadi Community Health Center, Asahan District. This study used a qualitative approach involving the head of the Community Health Center and the malaria program manager as respondents. The results showed that the management of malaria sufferers was quite good, but there were still obstacles in the availability of malaria drugs at the Sidodadi Health Center. Prevention and management of risk factors for malaria are also not optimal due to the lack of facilities and infrastructure for health workers. Epidemiological surveillance and epidemic control still need to be improved according to the standards of the Ministry of Health. Communication, information, and education in malaria prevention is quite good. The improvement of human resources at the Sidodadi Health Center has also been carried out well, but the Asahan District Health Office needs to continue to prioritize the malaria elimination program and continue to improve education for field workers. Keywords: Policy Implementation, Prevention, Malaria